The central cavity of ABCB1 undergoes alternating access during ATP hydrolysis. (1st April 2014) - van, Jessica H.; McMahon, Róisin M.; O'Mara, Megan L.; McDevitt, Christopher A.; Thomson, Andrew J.; Kerr, Ian D.; MacMillan, Fraser; Callaghan, Richard
<x xml:space="preserve">Abstract</x> Understanding the process that underlies multidrug recognition and efflux by P‐glycoprotein (ABCB1) remains a key biological challenge. Structural data have recently become available for the murine and Caenorhabditis elegans homologues of ABCB1; however all structures were obtained in the absence of nucleotide. A feature of these structures was the presence of a central cavity that is inaccessible from the extracellular face of the protein. To determine the conformational dynamics of this region several residues in transmembrane helices TM6 (331, 343 and 354) and TM12 (980) were mutated to cysteine. Based upon structural predictions, these residues are proposed to line, or reside proximal to, the central cavity. The mutant isoforms were labelled with a paramagnetic probe enabling the application of EPR spectroscopic methods. Power saturation EPR spectra were recorded in the presence of hydrophobic (O2) or hydrophilic (NiEDDA) quenching agents to study the local environment of each residue. ABCB1 was trapped in both its nucleotide‐bound and post‐hydrolytic conformations and EPR spectra were again recorded in the presence and absence of quenching agents. The EPR line shapes provide information on the movements of these residues within TM6 and TM12 during ATP hydrolysis. Rationalization of the data with molecular dynamic simulations indicates that the cavity is converted to a configuration open to the aqueous phase following nucleotide binding, thereby suggesting alternating access to the cavity on opposite sides of the membrane during translocation.